TEORI-TEORI PENDIDIKAN KONTEMPORER - Dalilan, Dalilan (Jurnal Bestari, 1993)
There are many improvements and developments in educational teories. In the with the course of the world, there is dialectical process in its affairs. Many philosophers and educators tends to compete to produce